PENINGKATAN KUALITAS LAYANAN PERGURUAN TINGGI SWASTA SERTA DAMPAKNYA TERHADAP KEPUASAN MAHASISWA - AGUSTIN HARI PRASTYOWATI; Saiful Amin (JABE (Journal of Applied Business and Economic), 2020)
This study aims to determine the quality of private education services and their impact on student satisfaction in Jember Regency. The research location is at the private collegesin Jember Regency. This research is a quantitative study using data collection techniques through questionnaires. The sampling technique uses Double Sampling, namely purposive sampling, and simple random sampling, with a total sample of 140 respondents obtained from the calculation of 6 variables with a total indicator of 22 multiplied by 6. The analytical method used is Multiple Linear Regression Analysis with Latent Variables so that it can be seen the level of student satisfaction with the services of the private colleges in Jember Regency. The results showed that the variable of empathy had an effect on student satisfaction at the private tertiary institution in Jember Regency. While the other four variables namely physical evidence, reliability, responsiveness, and guarantee had no effect on student satisfaction at the private colleges in Jember Regency.